INDIVIDUALIZAÇÃO JUDICIAL DA MEDIDA SOCIOEDUCATIVA DE INTERNAÇÃO NAS SENTENÇAS DA VARA DA INFÂNCIA E ADOLESCÊNCIA DE CAMPO GRANDE-MS - Ana Maria Assis de Oliveira (2022)
This research presents a study on the enforcement of fundamental law on judicial individualization of social-educative sentence of the adolescent author of infractions and the deprivation of liberty on judgment delivered in Campo Grande, Mato Grosso do Sul, at Childhood and Adolescence Court, during the year of 2019. The fundamental law mentioned is foreseen as individualization of penalty in Brazil Federal Constitution, whilst in Law 12.594 of 2012 it is extended as a guarantee to adolescents, as a principle of individualization of the socialeducative sentence. In the first two chapters there is a bibliographic survey on the recognition of the adolescent as a law subject and about the adolescents’ rights in Brazil. In the third chapter the study of the individualization of the social-educative sentence as a human and fundamental right is presented. The methodology applied to the research is the deductive, besides the exploratory and the descriptive ones in data analysis. It is possible to resume the central issue of this research with the question: How to produce, in praxis and law scope, the deprivation of liberty of adolescents and young adults in the sentences of offensive act verification, considering the fundamental right to judicial individualization of the social-educative sentence? The last chapter brings the result of the empirical research made through the analysis of 54 processes of verification of offensive acts, which represents the total amount of sentences with enforcement of the social-educative sentence of detention in the year of 2019 in the county of Campo Grande, to male gendered adolescents. As obtained result, the individualization was verified as an instrument of discretion in judicial decisions and the direct relation of the social context and life history to the deprivation of liberty.